Expression of IL-1β in transgenic Eimeria necatrix enhances the immunogenicity of parasites and promotes mucosal immunity against coccidiosis - Duan, Chunhui; Abudureheman, Tumalisi; Wang, Si; Suo, Jingxia; Yu, Ying; Shi, Fangyun; Liu, Xianyong; Salama, Dina B.; Srivastav, Ratnesh Kumar; Gupta, Nishith; Suo, Xun (Frontiers in Immunology, 2024)
Anticoccidial vaccines comprising living oocysts of Eimeria tenella, Eimeria necatrix, Eimeria maxima, and Eimeria acervulina are used to control coccidiosis. This study explored the potential of IL-1β to act as a molecular adjuvant for enhancing the immunogenicity of Eimeria necatrix and mucosal immunity. We engineered E. necatrix to express a functional chIL-1β (EnIL-1β) and immunized chickens with oocysts of the wild type (EnWT) and tranegenic (EnIL-1β) strains, respectively. The chickens were then challenged with EnWT oocysts to examine the immunogenicity-enhancing potential of chIL-1β. As expected, the oocyst output of EnIL-1β-immunized chickens was significantly reduced compared to those immunized using EnWT. No difference in body weight gain and lesion scores of EnIL-1β and EnWT groups was observed. The parasite load in the small intestine and caeca showed that the invasion and replication of EnIL-1β was not affected. However, the markers of immunogenicity and mucosal barrier, Claudin-1 and avian β-defensin-1, were elevated in EnIL-1β-infected chickens. Ectopic expression of chIL-1β in E. necatrix thus appears to improve its immunogenicity and mucosal immunity, without increasing pathogenicity. Our findings support chIL-1β as a candidate for development of effective live-oocyst-based anticoccidial vaccines.